(untitled) (Vallis Aurea, 2024)
Purpose of this study is to critically analyze the socio-ecological impact of water hyacinth on the water bodies passing through 7 wards of the Thrippunithura Municipality in the Ernakulam district of the state of Kerala, India, by checking the quality of water and conducting surveys among the people. Research Design The study employs a combination of exploratory and descriptive research approaches. Purposive sampling targets individuals directly impacted by water hyacinth proliferation. Methodology Data collection involved direct surveys using a structured questionnaire and water samples from selected regions. Results: reveal significant socio-economic ramifications of water hyacinth proliferation, particularly impacting fishing communities. Challenges include job losses, diminished access to fishing grounds, navigational hindrances, reduced catches, and fish scarcity. Ecologically, water quality parameters show notable disparities between heavily-infested and less-infested areas, highlighting the weed’s impact on aquatic ecosystems. The phytoremediation potential of water hyacinth was also explored, revealing its ability to accumulate heavy metals such as chromium, cadmium, copper, zinc, lead, iron, and arsenic. Originality of Research This study records the socio-ecological impact of water hyacinths on the communities and environment, particularly the water bodies, of the Greater Cochin area, Kerala, India.